2012
DOI: 10.1111/j.1440-1754.2012.02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of infants born to drug‐using mothers: A state‐wide audit

Abstract: Our regional study highlights a substantial prevalence of drug use in pregnancy with considerable adverse perinatal and hospital outcomes in infants born to these mothers. Coordinated health care and resources are needed to support these mother-infant pairs because of their social, medical and mental-health issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…Opioid-polydrug use during pregnancy is associated with a myriad of adverse outcomes for mothers and infants, such as increased odds of maternal death during hospitalization, placental abruption, preterm labor, Cesarean delivery, transfusion and extended hospital stays > 7 days (Maeda et al, 2014). It is also associated with prematurity, low birthweight, congenital anomalies, greater likelihood of pharmacological treatment of NAS, longer hospital stays, and higher risks for developmental problems (Abdel-Latif et al, 2013). Importantly, the association between mental health and substance use disorders must not be neglected when developing more efficient intervention strategies for the reduction of drug use during pregnancy; mental disorders and substance use disorders do not only have mutually exacerbating effects, but also contribute individually and synergistically to adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid-polydrug use during pregnancy is associated with a myriad of adverse outcomes for mothers and infants, such as increased odds of maternal death during hospitalization, placental abruption, preterm labor, Cesarean delivery, transfusion and extended hospital stays > 7 days (Maeda et al, 2014). It is also associated with prematurity, low birthweight, congenital anomalies, greater likelihood of pharmacological treatment of NAS, longer hospital stays, and higher risks for developmental problems (Abdel-Latif et al, 2013). Importantly, the association between mental health and substance use disorders must not be neglected when developing more efficient intervention strategies for the reduction of drug use during pregnancy; mental disorders and substance use disorders do not only have mutually exacerbating effects, but also contribute individually and synergistically to adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal treatment of NWS can require intensive care and prolonged hospitalisation 2 8. Opiate misuse during pregnancy is associated with preterm birth and poor fetal growth, but it is not clear whether these effects are caused by opiate misuse, other drug misuse or maternal mental health problems and/or an adverse environment 4 9. Compared with the general population, children born with NWS are at increased risk of neglect and other forms of child maltreatment during their childhood and their mother is more likely to die during their childhood 2 10…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the harmful effects on the fetus/child of maternal abuse of opiates or opioids during pregnancy, {e.g., 1,2] and when taken during the late part of pregnancy neonatal abstinence symptoms are common [3].…”
Section: Introductionmentioning
confidence: 99%